Eurya stigmosa (Theaceae), a new and extinct record for the Calabrian stage of Madeira Island (Portugal): 40Ar/39Ar dating, palaeoecological and oceanic island palaeobiogeographical implications. (15th February 2019) - Góis-Marques, Carlos A.; Mitchell, Ria L.; de Nascimento, Lea; Fernández-Palacios, José María; Madeira, José; Menezes de Sequeira, Miguel
Abstract: The general dynamic model of oceanic island biogeography (GDM) predicts the immigration, speciation and extinction of terrestrial biota through geological time on oceanic islands. Additionally, the glacial-sensitive model of island biogeography (GSM) also predicts extinction due to eustatic and climate change within islands. However, well-documented and natural pre-Holocene plant extinctions are almost unknown for oceanic islands worldwide. To test these predictions, we have sampled the Early Pleistocene Porto da Cruz lacustrine and fluvial sediments for plant fossils that could confirm the GDM and GSM extinction predictions. Additionally, two new 40 Ar/ 39 Ar geochronological analyses were performed, constraining the age of the sediments to 1.3 Ma (Calabrian). Among the fossils, Eurya stigmosa (R.Ludw.) Mai (Theaceae) seeds were recognised and studied by scanning electron microscopy (SEM). E. stigmosa is the first report of a natural (non-anthropogenic) extinct plant in the fossil record for Madeira Island, and for an oceanic island, confirming the GDM and GSM predictions. Eurya spp. palaeobiogeography indicates wider distribution in Europe until the end of the Pliocene (2.58 Ma), becoming extirpated to small refugia and extinct thereafter. The Madeiran record expands the formerly unknown presence of E. stigmosa to the Macaronesian realm. The new dating of the deposit at 1.3 Ma (Calabrian) means that E. stigmosa in Madeira was already in a refugium. The extinction in Madeira is most probably a combination of island ontogeny and climate change due to Pleistocene glaciations. The palaeoecological role of this extinct shrub or tree is currently unknown, but it was a probably an element of the Madeiran laurel forest, as this community was already present in Madeira at least 1.8 My ago. This new information corroborates the predictive power of GDM and GSM and adds a new view on the importance of studying oceanic island palaeobotany, specially palaeocarpofloras. Highlights: Eurya stigmosa (Theaceae) seed fossils are described for Madeira Island (Portugal). Two new 40 Ar/ 39 Ar dates constrain the age of fossils to 1.3 Ma (Calabrian). Madeira Island acted as a Quaternary refugium for the extirpated European Eurya . Madeiran Eurya fossils represent a pre-Holocene extinction in an oceanic Island. Fossils support current oceanic island biogeography models for natural extinctions.